Tamar's cry : re-reading an ancient text in the midst of a contemporary pandemic - Ackermann, D. M. (Dutch Reformed Theological Journal = Nederduitse Gereformeerde Teologiese Tydskrif, 2004)
In a first section, the story of Tamar is read from a woman's perspective, in a meditative, literary and canonical manner. In a second section, and against the backdrop of seeing HIV and AIDS in South Africa as "a gendered pandemic, " theological reflections are suggested that could contribute in the search for resistance and hope in the face of this bleak reality.
Paid